Dr. Ahmad Domocao Alonto an annotated bio-bibliography - Said, Pantonan M. (Institute of Library Science, University of the Philippines Diliman, 1981)
Rarely can a single individual live a varied life, all of which makes him great and respected by his people. Such is the rare personality of our subject, Dr. Ahmad Domocao Alonto. As a local traditional leader, being the son of the late Sultan of Ramain, a politician, a lawmaker, an educator, a pious leader of international repute, he has always remained true to his words and ideals for a united Philippines in diversity.